Front St., Dawson, Yukon Territory, approximately 1898 - Hegg, Eric A., 1867-1948 (1898)
Shows dogsled teams in front of "The Klondyke Miner Printing Office", Yukon Hotel Restaurant in background. Caption on image: "Front St. Dawson Y.T.". Klondike Gold Rush.